Pediatric Development and Neonatology A Practically Painless Review - Houser, Christine M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Often, information in review books can raise as many questions as it answers. This interferes with the study process, because the learner must either look up additional information or skip ahead without truly comprehending what he or she has read. As an alternative, Pediatric Development and Neonatology: A Practically Painless Review presents bite-sized chunks of information that can be read and processed rapidly, helping learners to stay active while studying to understand and process new information the first time they read it. This book's question and answer format allows for self-testing or study with a partner or a group. The format also facilitates dipping into the book during a few minutes of downtime at the hospital or office. Pediatric Development and Neonatology: A Practically Painless Review is a quick and easy way to master these tricky topics and is suitable for those studying for the pediatric board exam, practicing physicians brushing up on their skills, medical students and pediatric residents doing rotations, and any busy clinician who wants to learn more about these topics while on the go.
Developmental Topics -- Neonatal Physiology: Things That Make Them Special -- Brief Overview of Reproductive Embryology -- Cryptoorchism and Contraindications to Breast Feeding in Developed Nations -- Neonatal Topics.
Keywords: Medicine; Family medicine; Obstetrics; Maternal and infant welfare; Pediatrics; Medicine & Public Health; Pediatrics; Obstetrics/Perinatology.; General Practice / Family Medicine; Maternal and Child Health